2006
DOI: 10.1002/mc.20168
|View full text |Cite
|
Sign up to set email alerts
|

The role of NO synthases in arginine-dependent small intestinal and colonic carcinogenesis

Abstract: Arginine is catabolized by NOS2 and other nitric oxide synthases to form nitric oxide. We evaluated the roles of dietary arginine and Nos2 in Apc-dependent intestinal tumorigenesis in Min mice with and without a functional Nos2 gene. NOS2 protein was expressed only in intestinal tissues of Apc(Min/+) Nos2+/+ mice. NOS3 expression was higher in intestinal tissues of mice lacking Nos2, mainly in the small intestine. When diet was supplemented with arginine (0.2% and 2% in drinking water), lack of Nos2 results in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
40
1

Year Published

2006
2006
2010
2010

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 34 publications
(43 citation statements)
references
References 35 publications
2
40
1
Order By: Relevance
“…The mechanism and the role of polyamines in the regulation of NOS2 expression are unknown and should be addressed in further studies. A compensatory increase in intestinal but not colonic NOS3 expression in the absence of NOS2 was observed as reported previously by us (25). NOS3 was mainly localized to the nucleus and cytoplasmic expression was low in NOS2 knockout mice (25).…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…The mechanism and the role of polyamines in the regulation of NOS2 expression are unknown and should be addressed in further studies. A compensatory increase in intestinal but not colonic NOS3 expression in the absence of NOS2 was observed as reported previously by us (25). NOS3 was mainly localized to the nucleus and cytoplasmic expression was low in NOS2 knockout mice (25).…”
Section: Discussionsupporting
confidence: 84%
“…A compensatory increase in intestinal but not colonic NOS3 expression in the absence of NOS2 was observed as reported previously by us (25). NOS3 was mainly localized to the nucleus and cytoplasmic expression was low in NOS2 knockout mice (25). Because of this cellular distribution, polyamine uptake was likely not influenced by NOS3.…”
Section: Discussionsupporting
confidence: 84%
“…This result was similar to a report by Scott et al [35] that iNOS plays an antineoplastic role in a mouse model of familial adenomatous polyposis. However, our study was inconsistent with a previous report by Yerushalmi et al [36], who found that iNO derived from Arg promotes colonic tumorigenesis in congenital multiple intestinal neoplastic mice. The contradictory results related to iNOS involvement in colonic carcinogenesis may have resulted from different animal models.…”
Section: Discussioncontrasting
confidence: 79%
“…The contradictory results related to iNOS involvement in colonic carcinogenesis may have resulted from different animal models. In their experiment, elevated dietary Arg increased colonic NO and peroxynitrite concentrations, which can cause DNA damage resulting in mutagenesis and tumor initiation [36]. In our study, dietary Arg supplementation may have resulted in endogenous NO production by tumor cells and host cells, which may consequently have reduced tumor progression.…”
Section: Discussionmentioning
confidence: 87%
“…We believe the mice that died prior to study completion suffered from excessive adenoma burden of the small intestine. In future studies, we will incorporate treatments, such as arginine-enriched diets, to encourage lower rather than upper GI disease [16]. Because of the small amount of disease analyzed, additional studies must be performed to confirm these preliminary results.…”
Section: Imaging Notes and Challengesmentioning
confidence: 99%